Survei Kebutuhan Asuhan Kebidanan dalam Pelayanan Kesehatan Ibu dan Anak - Duhita, Fitra; Irianti, Bayu; Halida, Erda Mutiara; Hartiningtiyaswati, Setiya; Yulianti, Nova; Prabandari, Fitria; Anggraini, Yuliza; Yulita, Nova (Health Information : Jurnal Penelitian, 2023)
The development of services in various fields is always directed at the needs of its users, as an answer to the demands of the needs of the community. Midwifery care with mothers as the main users, so far has not met the needs of the community. This has an impact on the achievement of success indicators for mother and child services that have not met expectations. Therefore, it is necessary to know the needs of the community for midwifery care as a basis for improving midwifery care in Indonesia. This study aims to determine satisfaction with midwifery care. This study used a survey method, to find out the picture of maternal needs for midwifery care. The affordable population is mothers who receive midwifery care in several Puskesmas Kediri Regency, Bandung City, Padang City, Jakarta, Purwokerto, Surabaya and Tangerang. Sample selection was carried out by incidental sampling on all mothers who visited the maternal and child health poly (MCH) at the Puskesmas. The instrument used is a questionnaire. The data is analyzed and presented descriptively. Based on the data obtained, of the 604 mothers, it is known that only 2% (12) of mothers expressed satisfaction with the care provided by midwives. Further analysis per question item based on the aspect of care, it is known that the perception of aspects of care that are felt to be lacking is the cognitive aspect 18%, affective aspect 38% and skill aspect 44%. The care provided by midwives has not answered the needs of the community, as evidenced by the high level of maternal dissatisfaction with midwifery care.